Genetic Analysis for Early Diagnosis of Breast Cancer. - Amna Amin Sethi; Nisar Ahmed Shar (International Journal of Endorsing Health Science Research, 2024)
Background: Breast cancer is the most prevalent cancer type among women globally, constituting approximately 25% of all cancer cases. While germline mutations in BRCA1/BRCA2 genes are well-established risk factors for breast cancer, there remains a need to identify additional genes contributing to disease development. Understanding the genetic landscape beyond BRCA1/BRCA2 is crucial for elucidating disease heterogeneity and developing targeted therapies. Methodology: This study aimed to identify novel genes implicated in breast cancer development by analyzing genomic and clinical data from patients with six different breast cancer types. Utilizing various databases including NCBI, ENSEMBL, Clinical Variance, cBioPortal, COSMIC, DAVID, and OMIM, we conducted a comprehensive genetic analysis. Additionally, a survey was conducted to assess public perception of breast cancer. Results: Our genetic analysis revealed a significant overlap in genes associated with different breast cancer types, identifying NF1, PIK3CA, and TP53 as common genes across all types. Furthermore, the survey highlighted a lack of awareness regarding breast cancer causes and preventive measures among the general population. Conclusion: Beyond BRCA1/BRCA2, identifying common genes like NF1, PIK3CA, and TP53 sheds light on potential targets for therapeutic interventions across various breast cancer types. Promoting awareness and education, particularly on self-examination procedures, is imperative to empower individuals in breast cancer prevention and early detection efforts.